2009
DOI: 10.1017/s1368980008001924
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of selenium concentration and glutathione peroxidase activity in normal and breast cancer patients

Abstract: Objective: The present study was undertaken to compare plasma Se values and glutathione peroxidase (GPX) activity in normal and breast cancer patients. Design: In a case-control study, forty-five breast cancer patients and the same number of healthy women were randomly selected from their population. Se was measured in plasma by atomic absorption spectrophotometry and GPX activity in erythrocytes was measured using a standard spectrophotometric method. Results: Plasma Se concentration in healthy women and brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
2
6
0
2
Order By: Relevance
“…17 The association between Se and breast cancer has been studied for a long period, though previous research has not been conclusive. Similar to our results, Hunter et al (1990) and Moradi et al (2009) found no significant association between Se levels and breast cancer. 17,31 However, several studies, including Hardell et al (1993) and Rejali et al (2007) did find a significant association between low Se (in plasma and serum, respectively) and an increased risk of breast cancer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…17 The association between Se and breast cancer has been studied for a long period, though previous research has not been conclusive. Similar to our results, Hunter et al (1990) and Moradi et al (2009) found no significant association between Se levels and breast cancer. 17,31 However, several studies, including Hardell et al (1993) and Rejali et al (2007) did find a significant association between low Se (in plasma and serum, respectively) and an increased risk of breast cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our results, Hunter et al (1990) and Moradi et al (2009) found no significant association between Se levels and breast cancer. 17,31 However, several studies, including Hardell et al (1993) and Rejali et al (2007) did find a significant association between low Se (in plasma and serum, respectively) and an increased risk of breast cancer. 12,20 Two recent meta-analyses also suggest an association.…”
Section: Discussionsupporting
confidence: 90%
“…Not all studies observe a correlation between selenium deficiency and increased cancer incidence. Atomic absorption spectroscopy was used to determine the selenium concentration in blood samples from 45 patients with breast cancer and found no significant deficiency in selenium levels versus healthy controls [223].…”
Section: Cellular and In Vivo Studiesmentioning
confidence: 99%
“…On the other hand, a number of studies failed to find such relationships, or only found it in specific subgroups, such as smokers [11][12][13][14][15] .…”
Section: Observational Evidencementioning
confidence: 99%